The Impact of Receiving Price and Climate Information in the Agricultural Sector - Adriana Camacho; Emily Conover (Inter-American Development Bank (IDB), 2011)
Previous studies indicate that Colombian farmers make production decisions based on informal sources of information, such as family and neighbors or tradition. In this paper we randomize recipients of price and weather information using text messages (SMS technology). We find that relative to those farmers who did not receive SMS information, the farmers who did were more likely to provide market price information, had a narrower dispersion in the expected price of their crops, and had a significant reduction in crop loss. Farmers also report that text messages provide useful information, especially in regards to sale prices. We do not find, however, a significant difference between the treated and untreated farmers in the actual sale price, nor changes in farmers revenues or household expenditures.
Keywords: D62; Q11; Q12; Q13; 330